Marketing Research Scenario in Indian Corporate Sector - Jain, Kanubha (International Journal For Research In Business, Management And Accounting, 2016)
Known the standard of market research in India today, it is hard to believe that this ground wasalmost fictional about two decades ago. There was little focus on the customers, their wishes,likes and dislikes. In the absence of choices, sales were assured. Hence, there was almost noemphasis on research and development. Market Research provides an idea of the business andthe consumer market pattern. They tile the way to economic and business development and help to produce profit for the country. An extensive Market Research in India takes care of all thequeries of the marketers - giving them the required information for a soft marketing journey.Market research involves giving insight to all the categories of marketing - valuation,distribution, promotion of product and services. For betterment and upgradation, market researchis absolutely essential.